Linguistic and Cultural Mediation in the Context of Academic Mobility Abroad: A Systematic Review - Monroy, Sara Lucía (Íkala, Revista de Lenguaje y Cultura, 2024)
This article analyzes how functional the “mediation” category is in the context of higher education internationalization, as several research works report that international students must face multiple challenges during their academic stay abroad. To do this, we carry out a systematic review of empirical studies published between 2020 and 2023 that account for linguistic-cultural strains in international academic mobility scenarios. Particularly, we focus on conceptualizing the term “mediation”, what circumstances led to it, and which strategies were implemented to overcome barriers hindering intercomprehension. Drawing on the PRISMA statement guidelines, we designed a methodological path, which involved gathering together a sample of 43 entries for in-depth analysis. Findings reveal that implementing English as a medium of instruction in non-Anglophone countries is a stress factor in classrooms abroad. In response to this situation, translanguaging operates as the mediation strategy with the best potential to overcome communicational gaps in these scenarios as well as promoting multilingualism, inclusion, and educational equity for worldwide higher education. To conclude, we discuss the importance of universities including their research contributions on linguistic and cultural mediation in their language policy-making for local and international students.